Green Synthesis of ZnO Nanoparticles from Henna Leaves (Lawsonia inermis L.) and their Characterization as Photosensitizer in Dye-sensitized Solar Cells - W. S. Arsyad; F. S. Palobang; L Agusu; L. O. Rusman; I. Saleh; I N. Sudiana (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
The green synthesis of ZnO nanoparticles from henna leaf extract and their characterization as photosensitizers in dye-sensitized solar cells was successfully conducted. The henna leaves were extracted with three different solvents specifically distilled water (A), ethanol (E), and methanol (M). The extracts were mixed with Zinc Acetate dihydrate (Znac) with different concentrations of (0.01, 0.02, and 0.03) M to form ZnO nanoparticles. The absorbance spectrum, functional groups, and crystal structure were analyzed using UV-Vis, FTIR, and XRD. UV-Vis analysis revealed the highest absorption peaks at 580.74 nm, 503.63 nm, and 501.36 nm for samples A, E, and M. The FTIR spectrum of henna leaves confirmed the presence of Lawsone, indicated by O-H, C-H, C=O, and C-O functional groups at 3411 cm⁻¹, 2926 cm⁻¹, 1585 cm⁻¹, and 1344 cm⁻¹, respectively. XRD analysis showed the largest crystallite size (76.5 nm) for the 0.03 M Znac sample in methanol (M3), and the smallest (35.7 nm) for the 0.02 M Znac sample in ethanol (E2). The smallest energy gap (Eg) of 2.16 eV was observed in the sample using distilled water (A) as the solvent for the pure extract, while the ZnO nanoparticles (E1) sample had an Eg of 2.57 eV. We found that henna extract and the resulting ZnO nanoparticles were suitable to be used as photosensitizers in DSSC